Pengembangan E-LKPD Menulis Esai Berbasis Budaya Lokal Menggunakan Liveworksheets pada Siswa Kelas XI SMA Negeri 10 Palembang - Agnes; Nurhayati Nurhayati; Zahra Alwi (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to develop an interactive electronic student worksheet (E-LKPD) based on local culture, supported by Liveworksheets, focusing on argumentative essay writing material for eleventh-grade students at SMA Negeri 10 Palembang. The objectives of this study are to: (1) describe the results of the needs analysis of teachers and students regarding the development of an E-LKPD for essay writing based on local culture using the Liveworksheets application, (2) develop a design for the teaching material product of an E-LKPD for essay writing based on local culture using the Liveworksheets application, and (3) describe the results of the validity test of the developed E-LKPD for essay writing based on local culture using the Liveworksheets application. This study employs a development method based on the Alessi & Trollip model. Data collection techniques include interviews and questionnaire distribution to students and Indonesian language teachers. The product validation process was carried out by experts in the fields of content, media, and language. Based on the validation results, the content feasibility received a score of 73 with a percentage of 85.8%, along with suggestions to add examples of local culture-based essays, peer-review exercises, and additional material explaining essay structure. The language feasibility received a score of 49 with a percentage of 89%, with comments suggesting improvements and closer attention to language conventions (EYD). The media feasibility received a score of 64 with a percentage of 91.4%, with suggestions to improve the design of the cover and the school identity page. Revisions were made by the researcher in accordance with the validators’ feedback. Based on these validation results, it can be concluded that the electronic student worksheet (E-LKPD) based on local culture using Liveworksheets for teaching essay writing is highly feasible for use, categorized as highly valid.